Development Strategy of Jumog Waterfall as a Tourist Attraction in Karanganyar Regency, Central Java - Rahmawati Rahmawati; Hanugrah Kristiono Liestiandre; Matius Tinna Sarira; Hastuti Nurhayati; Faradila Anggun Surya Rini (Politeknik Pariwisata Makassar, 2024)
This study focuses on the development strategies of Jumog Waterfall as a tourist attraction in Berjo Village, Ngargoyoso District, Karanganyar Regency, Central Java. Known as the